Mathematical Models and Algorithms of Optimal Load Management of Electricity Consumers - I. U. Rakhmonov; K. M. Reymov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Load profile alignment based on optimal power consumption management is considered to be one of the main ways to ensure efficient operation of energy systems in the short-term planning. Alignment load profile with a view to reducing costs can be implemented with the aid of consumers’ involvement by administrative and economic measures. Administrative measures are associated with the forced restriction of consumer loads in certain intervals of the planning period. On one hand, these measures provide benefits to the power system by alignment load profile, and on the other hand, they cause detriment to consumers. Ultimately, in some cases, for the whole power system, the detriment may be greater than the benefits. Therefore, it is advisable to use administrative measures in conditions of shortage of power and electricity in the power system. Optimal planning of short-term regimes of power systems according to rigid load profile received after alignment can be carried out by traditional methods. The solution of such a problem ought to be initially carried out under conditions of non-rigid load profile resulting from the directive use of administrative and economic measures carried out with the help of specially developed models. In this regard, the paper proposes a mathematical model of the problem of optimizing load profile of regulated electricity consumers to be used for optimal planning of shortterm power system modes, an algorithm for optimal planning of a short-term power system mode with optimizing load profile of regulated power consumers. Also, algorithms are proposed for accounting for simple and functional constraints in the form of equalities and inequalities when optimizing load profile. The effectiveness of the described algorithm for optimizing the short-term mode of the power system, taking into account the optimal load control of adjustable electricity consumers, has been studied using the example of optimal coverage of the load profile of power system, which contains two consumers with adjustable load profile, and two TPPs. Based on the calculated-and-experimental studies, it was determined that the proposed mathematical model of the problem is adequate, while the developed algorithms for optimal planning of short-term power system modes with optimization of load profile of regulated electricity consumers and taking into account various types of limitations are of high computational qualities.